PENGEMBANGAN MODEL EDUKASI UNTUK BALITA STUNTING : SISTEMATIK REVIEW - Wa Ode Salma; Harleli Harleli; La Ode Alifariki (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
The first of six Global Nutrition Targets for 2025 is to reduce child stunting, which is a crucial indicator in the second Sustainable Development Goal of Zero Hunger. This systematic review was conducted based on the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) items. The search for relevant articles was conducted on five online databases, namely Google Scholar, PubMed, Wiley Online Library, Cochrane Library, and Science Direct. The search is performed on the Title and Abstract. All studies with evidence reporting on the implementation of educational models in stunting reduction and prevention efforts. Articles published from January 2015 to May 2021, written in English or Indonesian and published in peer reviewed journals. To assess the quality of the included studies, an assessment was conducted using the Critical Appraisal Skills Program (CASP). The included studies were divided into three categories of poor, moderate, and good to assess their quality. The search yielded 17,666 articles; after removing articles that are duplicates, there are 9,625 articles left. Furthermore, 9,617 articles were issued after screening titles and abstracts which did not match the included themes, which were letters/reports/short communications/chapters. The final screening resulted in 6 articles that met the inclusion criteria. This study provides an overview of several educational models that can be applied to the community.